Effect of Profitability, Audit Quality and Company Size on Audit Opinion Going Concern With Audit Lag as Intervening Variable - Wilsa Road Betterment Sitepu; Mega Irene; Jessy (Institute of Computer Science (IOCS), 2021)
The purpose of this study is to examine the effect of profitability, audit quality and company size on going concern audit opinions with audit lag as an intervening variable in basic and chemical industrial companies listed on the Indonesia Stock Exchange in 2017-2019, with a population of 80 companies and 31 samples. by using purposive sampling with the following criteria: basic and chemical industrial companies listed on the Indonesia Stock Exchange during 2017-2019 and not deleting, issuing complete reports, experiencing profits during 2017-2019. The research method uses quantitative methods and path analysis. And the results obtained that profitability and audit quality partially affect audit lag and audit quality has no effect on audit lag. And profitability, audit quality and company size partially affect going concern audit opinion, audit lag has no effect on going concern audit opinion, and audit lag is an intervening variable between the dependent and independent variables.